2020
DOI: 10.1007/s10531-020-02033-2
|View full text |Cite
|
Sign up to set email alerts
|

The Ancient Tree Inventory: a summary of the results of a 15 year citizen science project recording ancient, veteran and notable trees across the UK

Abstract: Ancient, veteran and notable trees are ecologically important keystone organisms and have tangible connections to folklore, history and sociocultural practices. Although found worldwide, few countries have such a rich history of recording and treasuring these trees as the UK, with its extensive Royal and aristocratic land ownership, unique land management methods and long-standing interest in natural history and species record collecting. As a result, the UK has collated an extensive database of ancient, veter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 70 publications
(75 reference statements)
0
43
1
1
Order By: Relevance
“…Compared to C. or N. Jiangsu, S. Jiangsu has the more subtropical humid monsoon climate, with higher mean annual temperature and more precipitation, which may be more suitable for the survival of heritage trees. Many studies have confirmed that ancient trees can better tolerate heat than drought [31,[48][49][50], especially in dry or hot seasons. The Shannon-Wiener diversity index (H) in S. Jiangsu is similar to that in N. Jiangsu, but each of them is higher than that in C. Jiangsu.…”
Section: Spatial Pattern Of Heritage Trees In Jiangsu Provincementioning
confidence: 99%
“…Compared to C. or N. Jiangsu, S. Jiangsu has the more subtropical humid monsoon climate, with higher mean annual temperature and more precipitation, which may be more suitable for the survival of heritage trees. Many studies have confirmed that ancient trees can better tolerate heat than drought [31,[48][49][50], especially in dry or hot seasons. The Shannon-Wiener diversity index (H) in S. Jiangsu is similar to that in N. Jiangsu, but each of them is higher than that in C. Jiangsu.…”
Section: Spatial Pattern Of Heritage Trees In Jiangsu Provincementioning
confidence: 99%
“…As a final step, the reliability and validity of each record in the ATI have previously been assessed by the Woodland Trust using a star rating system between one (least reliable) and five (most reliable; Table S1; Nolan et al, 2020). Consequently, we excluded all unverified (one or two star) records, and 185 records with incorrect or missing grid references.…”
Section: Study Area and Ancient Tree Recordsmentioning
confidence: 99%
“…Large old trees, depending on ecological context and geographical region, also referred to as giant, monumental, ancient, notable, oversized, or veteran trees, are keystone structures for the functioning and maintenance of the biological diversity of forests, woods, woodlands, and other landscapes, even those sparsely covered by trees, as well as urbanized [1][2][3][4][5]. However, their importance goes far beyond their ecological role.…”
Section: Introductionmentioning
confidence: 99%